Does internet reporting improve the accessibility of financial information in a global world? A comparative study of New Zealand and Indian companies - Chatterjee, Bikram; Hawkes, L. (University of Wollongong, 2008)
The accessibility of business reporting, including financial reports on company websites is not necessarily increased by providing more information on websites. The quality of Internet-based information is affected by both the accessibility and quantity of information provided. However, the accessibility of the information is an under researched area. This paper contributes to the existing body of knowledge on web-based business reporting, by considering the dimension of accessibility in terms of website appearance and visual design from four different perspectives. The aim is to consider the differences that occur in website organisation as a way of considering the accessibility of information provided on company websites. The paper considers the differences in the accessibility of website information between New Zealand and Indian companies as a means of demonstrating the variation that can occur across countries as well as within the same reporting structure. We conclude that Internet financial reporting does provide the illusion of comparability but without a more sustained focus on the harmonisation of terminology and attributes included in Internet reporting, the potential for comparison is reduced.